2012
DOI: 10.1021/ef301432q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Residual Particulates from Biomass Entrained Flow Gasification

Abstract: Biomass gasification experiments were carried out in a bench scale entrained flow reactor, and the produced solid particles were collected by a cyclone and a metal filter for subsequent characterization. During wood gasification, the major part of the solid material collected in the filter is soot. Scanning electron microscopy (SEM) images coupled with energy dispersive spectroscopy (EDS) show agglomerated nanosize spherical soot particles (<100 nm) that are very rich in carbon. In comparison to wood gasificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…This can explain the higher reactivity of char from 1400°C experiments compared to that from 1200°C, and also the higher reactivity of soot sample collected after 2 s of residence time compared to that of sample collected after 4 s of residence time for experiments at 1200°C. The same correlation between the increase of reactivity and mineral content with temperature, for soot from biomass pyrolysis, was also observed by Qin et al [18].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This can explain the higher reactivity of char from 1400°C experiments compared to that from 1200°C, and also the higher reactivity of soot sample collected after 2 s of residence time compared to that of sample collected after 4 s of residence time for experiments at 1200°C. The same correlation between the increase of reactivity and mineral content with temperature, for soot from biomass pyrolysis, was also observed by Qin et al [18].…”
Section: Discussionsupporting
confidence: 84%
“…The present study is an attempt to fill in the lack of information about char and soot in the context of biomass gasification in an en trained flow reactor. Only one recent work has been found in liter ature about this subject [18]. Characterization experiments were then performed on char and soot coming from wood particles pyrolysis in a drop tube reactor (DTR), a well adapted reactor to study biomass conversion in the conditions of an entrained flow reactor at lab scale.…”
Section: Introductionmentioning
confidence: 99%
“…A plot of ln(Àln(1ÀX) T À2 ) versus T À1 gives a straight line whose slope and intercept determine the values of the activation energy (E a ) and pre-exponential factor (A). The results of Qin et al [35] showed that a first order reaction model in both char mass and gasification agent can describe the experimental results well. The reactivities of wheat straw and rice husk chars were compared using reaction rates calculated for the derived kinetic parameters (A and E a ) at a fixed oxidation temperature of 400 C.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Indeed, soot gasification experiments have shown that soot gasification by steam was 2-20 times slower than char gasification between 750°C and 950°C [27]. Soot gasification by CO 2 is 2-30 times slower than char gasification at 1100°C [28].…”
Section: Char Gasificationmentioning
confidence: 99%